Relationship Based Procurement - Davis, Peter; Walker, D. (ARCOM, 2004)
Relationship based procurement leads to mutual benefit in construction business-to-business dealings and provides benefits over traditionally fragmented supply chains. Research in the area of Relationship Marketing (RM) provides an insight into key variables of collaboration and cooperation. These have the ability to enhance the construction procurement value chain. Further, theory on the creation of social capital and its role in generating intellectual capital between parties engaged in collaborative project procurement is explored. For example, Nahapiet and Ghoshal (1998) have argued that social capital comprises structural, cognitive and relationship dimensions and that through combination and exchange of this social capital intellectual property is created that leads to organisational advantage. Social and intellectual capital adds an intangible benefit to participating in a relationship based procurement systems. Project alliances are a particular kind of relationship procurement system that rely on virtual organisations generating new knowledge enabling teams to solve interrelated problems in a complex environment. Utilising the theory described an insight into alliance projects recently carried out in Australia is provided drawing on contemporary construction literature. Instances are described where the RM literature together with social capital knowledge fills gaps in the construction literature.